Diagnóstico de seguridad vial en la avenida las américas en la ciudad de Duitama - Chia Gomez, Laura Valentina; Patiño Bello, Sergio Nicolas (Universidad Antonio Nariño, 2023)
Road safety is composed of a set of measures implemented to keep the road infrastructure operating safely, some of the most commonly used measures are speed reduction, the adoption of an adequate geometric design and the adoption and enforcement of these measures by the driver. For these policies to be effective, they must be focused, so it is necessary to analyze the points of the road network where accidents are most concentrated, so that the most relevant variables of these events can be defined and included for their strategic mitigation. The purpose of this project is to focus future measures to reduce accidents in a city like Duitama, evaluating one of the main corridors, which is located between the hospital traffic circle (Circumvalar Avenue) and the cemetery traffic circle (Carrera 16). The methodology used to perform this analysis includes the comparison of the variables recorded in the accident rate data with the information collected in the field; through road safety inspections, it was found that the main causes of the accident rate in the corridor were related to the lack of adequate infrastructure and the behavior of users, mainly pedestrians and drivers.